Dynamics of social capital among irrigation water users in rural Sindh province of Pakistan - Sheikh, Javed M.; Magsi, Habibullah; Abu Samah, Asnarulkhadi; Khusk, G. Mujtaba; Qureshi, Naeem A. (University of Technology, Sydney and Xi'an University of Architecture and Technology, 2016)
Social capital resides in interactions and refers to social resources and network structure. It develops trust, reciprocity and functions as bonding material to provide long term and sustainable results, however, fluctuates spatially and culturally. In connection with, the article attempted to reveal the various levels of social capital between farmers in participatory irrigation management, via a trust, solidarity and networks, and also supported by the theoretical perceptive. Consequently, quantified data were gathered from 457 irrigation water users of rural Sindh province, using multi-stage cluster sampling, and analyzed through SPSS (Software Package for Social Sciences) and AMOS (Analysis of Moment Structures) software. This paper reports the significant results regarding social capital in the area, which reflects in the form of reciprocity of irrigation water by the respondents. In contrast, the majority of the farmers were lacking linking social capital which must be reviewed by the policymakers for the sake of rural development.